A preliminary investigation into hybrid photovoltaic cells with organic phthalocyanines and amorphous silicon heterojunction. (2nd April 2015) - Zhao, Huan; He, Zhiqun; Zhang, Xiaojin; Zhang, Zhi; Diyaf, Adel; Lind, Anna H N; Liang, Chunjun; Wilson, John I B
Abstract: Hybrid photovoltaic cells take the advantages of silicon in charge carrier separation and transport and organic dyes in strong complementary light absorption. Photovoltaic responses from a set of hybrid solar cells based on amorphous silicon and phthalocyanine dyes of double- or triple-layer heterojunction structures were investigated, which were found to have thickness dependence with the organic active layers. It was found that the photocurrent contributions from organic layers are limited, although they are strong light absorbers. The main photocurrent contributions are from the silicon counterpart.